Organizing Transmission Belts: The Effect of Organizational Design on Interest Group Access to EU Policy‐making*. (6th January 2019) - Albareda, Adrià; Braun, Caelesta
Abstract: The European Commission's outreach to interest groups implies that they function as 'transmission belts' that aggregate and articulate interests as policy‐relevant information for policy‐makers. Operating as a transmission belt, however, requires an organizational design fit for this purpose. We offer one of the first systematic analyses of how organizational design affects interest group access to public officials. We draw from a novel dataset of 248 EU‐level interest groups including data on several dimensions of organizational design. One of our key findings is that qualified majority and consensus‐facilitating decision‐making procedures help interest groups gain access to administrative and political officials, whereas functional differentiation is important to get access to administrative officials, but not to political officials. Our findings thus demonstrate the relevance of organizational design in gaining access as well as the need to incorporate varying informational demands of public officials to properly explain interest group access to public decision‐making.